Face and mask : a double history - Belting, Hans (Princeton University Press, 2017)
This fascinating book presents the first cultural history and anthropology of the face across centuries, continents, and media. Ranging from funerary masks and masks in drama to the figural work of contemporary artists including Cindy Sherman and Nam June Paik, renowned art historian Hans Belting emphasizes that while the face plays a critical role in human communication, it defies attempts at visual representation. Belting divides his book into three parts: faces as masks of the self, portraiture as a constantly evolving mask in Western culture, and the fate of the face in the age of mass media. Referencing a vast array of sources, Belting's insights draw on art history, philosophy, theories of visual culture, and cognitive science. He demonstrates that Western efforts to portray the face have repeatedly failed, even with the developments of new media such as photography and film, which promise ever-greater degrees of verisimilitude. In spite of sitting at the heart of human expression, the face resists possession, and creative endeavors to capture it inevitably result in masks--hollow signifiers of the humanity they're meant to embody. From creations by Van Eyck and August Sander to works by Francis Bacon, Ingmar Bergman, and Chuck Close, "Face and Mask" takes a remarkable look at how, through the centuries, the physical visage has inspired and evaded artistic interpretation.